Digital generation representatives of various professional success levels: psychological features - Pishchik Vlada; Postnikova Margarita (E3S Web of Conferences, 2020)
The article presents the values of the individual psychological features of sales managers, reinforcing their professional effectiveness. The novelty lies in the fact that the individual psychological features of managers belonging to the digital generation, manifested in mental activity, interpersonal relationships and emotional reactions to the effects of the environment were studied. The following methods were used: the method of determining of the types of thinking and the level of creativity by G. Bruner, self-assessment of mental states by H. Eysenck, diagnostics of interpersonal relationships by T. Leary, test «Motivational profile» by Sh. Richie and P. Martin, PSM25 by Lemour-Tessier-Fillion adapted by N.E. Vodopyanova, the technique of diagnostics of the type of the emotional reaction to the stimuli of the environment by V. V. Boyko. We calculated primary statistics and used the criteria analysis applying the Student's t-test. The results showed that: there are significant differences in individual psychological peculiarities of sales managers with different levels of professional efficiency. Effective managers are more aggressive, more closed, do not seek long-term relationships, financially oriented, have a need for achievements, recognition. Ineffective managers are more rigid, anxious, frustrated, aggressive, seek structured work, focused on long-term relationships, have a low need for self-improvement.